New Frontiers in Three-Dimensional Culture Platforms to Improve Diabetes Research - Sundhar Mohandas; Vijaya Gayatri; Kriya Kumaran; Vipin Gopinath; Ramasamy Paulmurugan; Kunka Mohanram Ramkumar (MDPI AG, 2023)
Diabetes mellitus is associated with defects in islet β-cell functioning and consequent hyperglycemia resulting in multi-organ damage. Physiologically relevant models that mimic human diabetic progression are urgently needed to identify new drug targets. Three-dimensional (3D) cell-culture systems are gaining a considerable interest in diabetic disease modelling and are being utilized as platforms for diabetic drug discovery and pancreatic tissue engineering. Three-dimensional models offer a marked advantage in obtaining physiologically relevant information and improve drug selectivity over conventional 2D (two-dimensional) cultures and rodent models. Indeed, recent evidence persuasively supports the adoption of appropriate 3D cell technology in β-cell cultivation. This review article provides a considerably updated view of the benefits of employing 3D models in the experimental workflow compared to conventional animal and 2D models. We compile the latest innovations in this field and discuss the various strategies used to generate 3D culture models in diabetic research. We also critically review the advantages and the limitations of each 3D technology, with particular attention to the maintenance of β-cell morphology, functionality, and intercellular crosstalk. Furthermore, we emphasize the scope of improvement needed in the 3D culture systems employed in diabetes research and the promises they hold as excellent research platforms in managing diabetes.